LITERARY TRANSLATION AS PERFORMANCE. THEORETICAL QUESTIONS AND A LITERARY ANALOGY - Locatelli, Angela (Armenian Folia Anglistika, 2021)
The aim of this essay is to propose a view of literary translation as “performance”, i.e., as both an art and an activity endowed with specific affinities with those of the actor or the musician. Actors and musicians offer subjective interpretations of the dramatic texts and of the musical scripts that they present on stage and in the concert hall. Likewise, the translator presents her/his interpretation and her/his rendering of a specific text to readers whose mother tongue and culture may either be close or remote from the ones of the original. In other words, a translator of artistic literature is ‘a performer’ and each translation an ‘execution’ i.e., a unique ‘rendering of the script’ (T1), and it is both a recognizable prior text (T1) and yet also a specific variation of it (T2). After some theoretical observations on translation (Part 1 of the essay), my thesis will be developed in connection with an interpretation of the character of Bottom, the weaver-actor in A Midsummer Night’s Dream, because his experience and ‘personality’, seem to bear interesting metaphorical affinities with those of the translator as performer of poetic texts (Part2 of the essay).
Keywords: translation; performance; aesthetic enjoyment; theory and poetics of translation; literature; Shakespeare